2012
DOI: 10.1542/peds.2011-1796
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Antecedents of Cognitive Impairment at 24 Months In Extremely Low Gestational Age Newborns

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Among extremely premature infants, survival has improved, but the rate of cognitive impairment has not. Impaired cognition is the most frequent developmental problem identified in survivors. Several antenatal factors have been associated with cognitive impairment, mostly related to social disadvantage. WHAT THIS STUDY ADDS:In addition to social disadvantage, antenatal characteristics associated with cognitive impairment include maternal obesity and thrombosis of fetal stem vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 57 publications
2
55
2
Order By: Relevance
“…Recent studies, however, have highlighted a role for both earlier and subtler insults in the majority of cases. For example, the Extremely Low Gestational Age Newborns (ELGAN) Study reported that severe intrauterine growth restriction and evidence of placental vascular thrombosis were associated with impaired neurodevelopmental outcome at 2 y of age (19), consistent with a role for long-standing, prenatal hypoxia. After birth, although low blood pressure is common, the evidence for an association between hypotension and adverse outcomes is limited, as reviewed earlier (20).…”
Section: Mechanisms Of Perinatal Brain Injurymentioning
confidence: 99%
“…Recent studies, however, have highlighted a role for both earlier and subtler insults in the majority of cases. For example, the Extremely Low Gestational Age Newborns (ELGAN) Study reported that severe intrauterine growth restriction and evidence of placental vascular thrombosis were associated with impaired neurodevelopmental outcome at 2 y of age (19), consistent with a role for long-standing, prenatal hypoxia. After birth, although low blood pressure is common, the evidence for an association between hypotension and adverse outcomes is limited, as reviewed earlier (20).…”
Section: Mechanisms Of Perinatal Brain Injurymentioning
confidence: 99%
“…Nevertheless, there is some evidence for a role of subtle insults, as shown, e.g., by depressed Apgar scores at birth (22). More recently, the Extremely Low Gestational Age Newborns (ELGAN) study reported that severe intrauterine growth restriction and evidence of placental vascular thrombosis consistent with longstanding, prenatal hypoxemia were associated with impaired neurodevelopmental outcome at 2 y of age (23). After birth, although low blood pressure is common, the evidence for an association between hypotension and adverse outcomes is limited, as reviewed in ref.…”
Section: Timing and Etiology Of Preterm Brain Injurymentioning
confidence: 99%
“…The clinical relationship between injury and infection is complex and closely intertwined with placental insufficiency [10,11,12]. This complexity is mirrored by preclinical evidence in the neonatal rat that single-dose exposure to lipopolysaccharide (LPS) can either protect or sensitize to injury from other insults [13,14,15,16,17], depending on the time interval between exposure to infection and subsequent ischemia.…”
Section: Introductionmentioning
confidence: 99%